Single- and double-tunnel endoscopic submucosal tunnel dissection for large superficial esophageal squamous cell neoplasms - Zhang, Wengang; Zhai, Yaqi; Chai, Ningli; Linghu, Enqiang; Li, Huikai; Feng, Xiuxue (Endoscopy, 2018)
Background and study aim Single-tunnel endoscopic submucosal tunnel dissection (ESTD) has shown promising preliminary efficacy for large superficial esophageal squamous cell neoplasms (SESCNs). This study reports the outcomes of both single- and double-tunnel ESTD for large SESCNs, and compares the efficiency of the two techniques for treating circumferential SESCNs.Patients and methods 46 patients with large SESCNs underwent ESTD at a single hospital between October 2011 and March 2016. Relevant clinical data were retrospectively collected and analyzed.Results For all patients, the en bloc and R0 resection rates were 95.7 % and 82.6 %, respectively. Perforation and cardiac mucosal laceration were detected in 2.2 % (1/46) and 6.5 % (3/46) of the procedures, respectively. Postoperative stenosis occurred in 12 patients (26.1 %). Of the 18 patients with circumferential lesions, those who received a double-tunnel ESTD procedure (n = 6) underwent dissection faster than those who had a single-tunnel ESTD procedure (n = 12) (0.32 vs. 0.12 cm2/min; P = 0.02). Conclusion ESTD was effective for large SESCNs. The double-tunnel ESTD appeared to decrease operative time compared with single-tunnel ESTD for circumferential lesions.